Temperature Dependence of Pressure Derivatives of Higher Order Elastic Constants of TeO Crystal - Kumar, Jitendra; Kumar, Virendra; Chaudhary, A.K.; Kailash (Asian Journal of Chemistry, 2011)
A proper and systematic evaluation of the elastic constants of isostructural oxides and their dependence on temperature provides the fundamental data for determining the characteristics of cation-oxygen bonding interactions, which are pertinent to the understanding and theoretical modelling of more complicated oxide compounds. The information about higher order elastic constants is valuable in understanding nature of short range forces in crystals. Tellurium oxide is a divalent crystals and possess FCC crystal structure. In this work, an attempt has been made to evaluate higher order elastic constants for tellurium oxide at an elevated temperature starting from 50 K to near its melting point. The melting point for tellurium oxide is 643 K. The data of second, third and fourth order elastic constants (SOECs, TOECs and FOECs) are used to evaluate the first order pressure derivatives (FOPDs) of SOECs and TOECs, second order pressure derivatives (SOPDs) of SOECs and partial contractions. While evaluating these properties it is assumed that the crystal structure does not change during temperature variation. The data of these oxides obtained through different techniques also give important and valuable information about internal structure and inherent properties of materials and can be used in future for different industrial purposes and further investigations of divalent FCC structured solids and other isostructural oxides.